Honeycomb micro/nano-architecture of stable β-NiMoO4 electrode/catalyst for sustainable energy storage and conversion devices. (6th November 2020) - Padmanathan, N.; Shao, Han; Razeeb, Kafil M.
Abstract: Multi-functionality is a highly desirable feature in designing new electrode material for both energy storage and conversion devices. Here, we report a well-integrated and stable β-NiMoO4 that was fabricated on three dimensional (3D) nickel foam (NF) by a simple hydrothermal approach. The obtained β-NiMoO4 with interesting honeycomb like interconnected nanosheet microstructure leads to excellent electrochemical activity. As an electrode for Supercapatteries, β-NiMoO4 –NF showed a high specific capacity of 178.2 mA h g −1 (916.4 F g −1 ) at 5 mA cm −2 current density. Most importantly, the fabricated symmetric device exhibits a maximum specific energy of 35.8 W h kg −1 with the power output of 981.56 W kg -1 and excellent cyclic stability. In methanol electro-oxidation, the β-NiMoO4 –NF catalyst deliver the high current density of 41.8 mA cm −2 and much lower onset potential of 0.29 V with admirable long term stability. Apart from the above electrochemical activity, the β-NiMoO4 –NF honeycomb microstructure demonstrates a promising non-noble electrocatalyst for oxygen evolution reaction (OER) and hydrogen evolution reaction (HER) and showed a considerable overpotential of 351 mV (OER) and 238 mV (HER). The attractive multifunctional electrochemical activity of β-NiMoO4 –NF could be originates from their unique honeycomb micro/nano structure which can acts as an "ion reservoir" and thus leads to superior energy storage and conversion processes. Highlights: Honeycomb like β-NiMoO4 microstructure was grown over 3D-nickel foam. Multi-functionality of β-NiMoO4 for supercapattery and methanol oxidation was investigated. Supercapattery has delivered energy and power of 35.8 W h kg −1  and 981.56 W kg -1 . Ternary β-NiMoO4 showed excellent methanol electro-oxidation with low onset potential. Graphical abstract: Image 1